ECONOMIC EFFICIENCY OF REDUCTION IN SYPHILIS AND HONORRHEA MORBIDITY - A. D. Botvinkin; N. A. Dolzhenitsina; A. A. Safyannikova; N. A. Shpakova; M. B. Dmitrieva (Acta Biomedica Scientifica, 2017)
After the epidemic in the middle of 1990-s, incidence of syphilis in Irkutsk region reduced from 432.4 in 1997 to 66.4 in 2013. At the same time incidence of gonorrhea reduced from 375.9 in 1993 to 75.8 in 2013 per 100,000 of population. About 10 000 cases of gonorrhea and 12 000 cases of syphilis are reported annually during the pick of the epidemic. We used cost-benefit analysis to estimate the economic efficiency of regional morbidity reduction. The costs were adjusted to 2013 year prices. Average direct and indirect costs per case were as follows: syphilis 23.2 and gonorrhea 7.1 thousand rubles. Reductions in syphilis and gonorrhea from maximum in the middle of 1990-s to 2013 have saved about 300 million rubles approximately. In 2005-3013 the costs reduction was estimated as 10 million rubles per year. This sum composed about 20 % of total subsidy from federal budget to Irkutsk region for struggle with sexually transmitted infections (STI). Per year correlation between sum of subsidy for struggle with STI and number of syphilis cases composed -0.54 and -0.55 of gonorrhea cases (p > 0.05). Social factors also were discussed among reasons of morbidity reduction. In 2005-2013 regional income and birth-rate in Irkutsk region were increasing in contrast with the middle of 1990-s.